Inhaled nano- and microparticles for drug delivery - El-Sherbiny,IM; El-Baz,NM; Yacoub,MH (Global Cardiology Science and Practice, 2015)
The 21st century has seen a paradigm shift to inhaled therapy, for both systemic and local drug delivery, due to the lung's favourable properties of a large surface area and high permeability. Pulmonary drug delivery possesses many advantages, including non-invasive route of administration, low metabolic activity, control environment for systemic absorption and avoids first bypass metabolism. However, because the lung is one of the major ports of entry, it has multiple clearance mechanisms, which prevent foreign particles from entering the body. Although these clearance mechanisms maintain the sterility of the lung, clearance mechanisms can also act as barriers to the therapeutic effectiveness of inhaled drugs. This effectiveness is also influenced by the deposition site and delivered dose. Particulate-based drug delivery systems have emerged as an innovative and promising alternative to conventional inhaled drugs to circumvent pulmonary clearance mechanisms and provide enhanced therapeutic efficiency and controlled drug release. The principle of multiple pulmonary clearance mechanisms is reviewed, including mucociliary, alveolar macrophages, absorptive, and metabolic degradation. This review also discusses the current approaches and formulations developed to achieve optimal pulmonary drug delivery systems.